The impact of online learning implementation on satisfaction, motivation, quality of the learning process, and student learning outcomes - Tri Wintolo Apoko; Mohammad Balya Ali Sya'ban (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to find out whether online learning contributes to student learning satisfaction, whether online learning has a positive influence on students' learning motivation, whether online learning has a significant influence on the quality of the learning process, and whether online learning has a positive impact on student learning outcomes. The research method used is a survey method, which collects respondent data as a research sample and is processed with statistical data and presentation in the form of graphs and percentage figures. The instruments used in this study are questionnaires to find out or measure the level of satisfaction, motivation, and quality of the learning process and documents in the form of student learning outcome scores (midterm test scores). The instrument used is created in the form of a Google form (GF) to reach student data online. The population of this study is all students of the Faculty of Teacher Training and Education UHAMKA in semesters 2, 4, and 6. While the research sample was 1007 out of the total number of active students as many as 4042. The results showed that (1) the level of satisfaction of FKIP UHAMKA students to online learning was 52.53%, (2) student motivation for online learning by 54.51%, (3) the quality of the online learning process by 56.10, and (4) student learning outcomes through online learning increased by 96.21%. Therefore, it was concluded that online learning has a positive impact on learning motivation, the quality of the learning process and student learning outcomes.